Ruled surfaces generated by elliptic cylindrical curves in the isotropic space - Aydin, Muhittin Evren; Mihai, Adela (Walter de Gruyter Gmbh, 2019)
In this paper we study the ruled surfaces generated by elliptic cylindrical curves in the isotropic 3-space I-3. We classify such surfaces in I-3 with constant curvature and satisfying an equation in terms of the components of the position vector field and the Laplacian operator. Several examples are given and illustrated by figures.
Keywords: Ruled surface; elliptic cylindrical curve; isotropic space; isotropic mean curvature; relative curvature; Laplacian operator